Direct numerical simulation of helical vortices. (1st January 2012) - Delbende, Ivan; Rossi, Maurice; Piton, Benjamin
We herein present a direct numerical simulation method aimed at describing the dynamics of helical vortices such as those developing in the wake of propellers and wind turbine or helicopter rotors. By enforcing a helical symmetry, the 3D incompressible Navier-Stokes equations are reduced to a 2D problem which we solve using a generalised vorticity/streamfunction formulation. In this framework, we simulate the viscous dynamics of one or several helical vortices and describe quasi-steady states as well as long-time (or far-wake) dynamics. In particular, several types of merging in the two helical vortex systems are identified.